Postoperative Management of Cleft Lip and Palate Surgery - Raghavan, Ullas; Vijayadev, Vishwas; Rao, Dipesh; Ullas, Gautham (Facial Plastic Surgery, 2018)
Cleft lip and palatal clefts are one of the most common birth defects with a global incidence of 1 in 700 live births. The majority of these orofacial clefts are nonsyndromic. However, a general screening for syndromes and other organ anomalies should always be performed as their association with orofacial clefts cannot be overlooked. With the recent progress in the knowledge of cleft repair, the procedures to correct cleft lip and palate though complex, have been simplified to allow improvisation in outcome and to achieve even better finesse of surgical result. The procedural complications and the pursuit of having near perfect esthetics and functionality, make this deformity a recipient of multiple procedures. This ensures that the patient is under the care of the treating surgeon for long term and allows the surgeon to follow-up on the result, not only to provide care but also to intercept any deviation in the desired outcome. Postoperative care of cleft lip and palate surgery is largely underdiscussed and a set of fixed guidelines will help the treating surgeon to provide the most comprehensive care to the cleft patients. The authors review the practices followed at their hospitals—a high volume cleft and craniofacial care center, a tertiary care multispeciality teaching hospital, and a community teaching and training hospital. The commonly followed practices with suitable evidence in postoperative care of these patients are enlisted here.
Keywords: cleft lip; cleft palate; postoperative care; outcome; guidelines